Efektivitas Pembelajaran Tatap Muka Pada Mata Pelajaran PAI Pada Masa Pandemi Covid-19 di SMK Tamtama 2 Prembun - Mustajibur Rohman; Eliyanto Eliyanto; Nginayatul Khasanah (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
The purpose of this study was to determine the effectiveness of face-to-face learning at SMK Tamtama 2 Prembun and to find out how to determine the face-to-face learning method during the COVID-19 pandemic at SMK Tamtama 2 Prembun. This research is a field research conducted at SMK Tamtama 2 Prembun with a qualitative approach. By using a qualitative approach, and using data collection techniques of observation, interviews, and documentation. Based on the results of the research on the effectiveness of face-to-face learning in PAI subjects during the Covid-19 pandemic as follows. (1) Face-to-face learning on PAI subjects during the Covid-19 Pandemic is less effective because the time allocation is shortened. (2) The method used by PAI teachers at SMK Tamtama 2 Prembun in teaching face-to-face learning during the Covid-19 pandemic was using the lecture method.